Service life planning for affordable housing design: a challenge to Malaysian construction industry - Tapsir, Siti Hamisah; Usman, Fathoni (2007)
Traditionally the construction industry has been expected to provide buildings and constructed assets that are of quality finishes, cheaper, faster to build and durable. With the rising of technology and concern for environment, increasing attention is given on sustainability. As the overall performance of building relies on the service life and performance of its component and materials, research on method for predicting the service life of construction component and materials is on going globally. Balance quality and sustainability to attempt affordability in residential housing is prior challenge to the construction industry. This paper will describe roughly condition of local housing industry and the global issue of sustainability in line to the ISO on service life planning. Theoretical approach to estimates the service life of building component and ongoing research on service live at Universiti Teknologi Malaysia will be the bridge to occupy the challenge.